A novel method for genetic transformation of yeast cells using oligoelectrolyte polymeric nanoscale carriers. (January 2013) - Filyak, Yevhen; Finiuk, Nataliya; Mitina, Nataliya; Bilyk, Oksana; Titorenko, Vladimir; Hrydzhuk, Olesya; Zaichenko, Alexander; Stoika, Rostyslav
The genetic transformation of target cells is a key tool in modern biological research, as well as in many gene therapy and biotechnology applications. Here we describe a new method for delivery of DNA into several industrially important species of yeast, including Saccharomyces cerevisiae . Our method is based on the use of a novel nanoscale oligoelectrolyte polymer possessing a comb-like structure as a carrier molecule. Direct comparisons to standard transformation methods clearly show that our approach: (i) yields two times more transformants of Hansenula polymorpha NCYC 495 compared to electroporation approaches and 15 times more transformants compared to lithium acetate protocols, as well as (ii) 5 times more Pichia pastoris GS115 transformants compared to electroporation and 79 times more transformants compared to lithium acetate. Taken together, these results clearly indicate genetic transformation of yeasts using oligoelectrolyte polymer carriers is a highly effective means of gene delivery.